UJI FITOKIMIA, TOKSISITAS (BRINE SHRIMP LETHALITY TEST) SERTA ANTIOKSIDAN KULIT BATANG TERAP (Artocarpus elasticus reinw) DENGAN METODE DPPH (2,2-diphenyl-1-picrylhidrazyl) - Maulidya Hafsari Fauzi; Erwin Erwin; Irawan W. Kusuma (PROSIDING SEMINAR KIMIA, 2017)
Phytochemical test, the mortality of larvae shrimp (Brine Shrimp Lethality Test) and antioxidant activity test of secondary metabolites stem bark of Terap (Artocarpus elasticus reinw) by several of method such as extraction, phytochemical test, the mortality of larvae shrimp (Brine Shrimp Lethality Test) and antioxidant activity test. Based on the result of Brine Shrimp Lethality Test was analyzed using SAS probit analysis to know the value of Lethal Concentration 50 % (LC50), Brine Shrimp Lethality test result that the fraction of ethyl acetate has the highest toxicity with LC50 value obtained 153,3788 ppm. Based on the results of antioxidant activity test that ethanol extract has the highest antioxidant activity with IC50 value obtained at 70.59 ppm. Based on the Phytochemical test, the mortality of larvae shrimp (Brine Shrimp Lethality Test) and antioxidant activity test , it was obtained secondary metabolite compound of phenolic active in stem bark of Terap. Keywords: Terap (Artocarpus elasticus reinw), Brine Shrimp Lethality Test, Antioxidant Activity test.